Role of Circulating Tumor DNA Among Patients with Colorectal Peritoneal Metastases - Baumgartner, Joel M.; Botta, Gregory P. (Journal of gastrointestinal cancer, 2024)
Purpose This was a review of circulating tumor DNA (ctDNA) in patients with peritoneal metastases from colorectal cancer. Methods We searched the PubMed database for studies reporting detection of ctDNA in patients with colorectal cancer (CRC) and with peritoneal metastases (PM) from colorectal cancer (CRPM). We extracted data on the population included, number of subjects, study design, type of ctDNA assay used and schedule, and the major findings from these publications. Results We identified 13 studies for review investigating ctDNA, using a variety of ctDNA assays, among 1787 patients with CRC without PM, as well as four eligible published and one unpublished (in press) studies, which included 255 patients with PM from any primary site and 61 patients with CRPM. Among the 13 studies investigating ctDNA among CRC without PM, posttreatment surveillance ctDNA was associated with recurrence and was generally more sensitive than imaging or tumor markers. Among the five studies including patients with PM, ctDNA was not universally able to detect the presence of PM, but when present, ctDNA predicted worse outcomes. Conclusion Circulating-tumor DNA is a potentially useful surveillance tool for patients with CRC. However, the sensitivity of ctDNA to detect CRPM is variable and warrants further inquiry.